(untitled) - Haley, Mike; (1962-...) (U.S.A., 2004)
For many, homosexuality isn't just a societal issue .. it's very personal. A son or daughter reveals a long-standing struggle with same-sex attraction, a husband leaves his wife for another man, or a coworker shows up at the office picnic with her female lover. In every case, there are questions we want to ask but are reluctant to voice. Here are the answers to the most often asked questions about homosexuality from an expert on the subject -- and a former homosexual himself -- Focus on the Family's Mike Haley. Whether you're personally impacted by homosexuality or simply concerned about this controversial issue .. you'll be informed and challenged by these 101 thoughtful questions and answers.
Keywords: Trivia and miscellaneous